EVALUATION OF ALONGSHORE SEDIMENT TRANSPORTS AT PANTAI TELUK NIPAH, PANGKOR ISLAND - Lim Yong, Benjamin Hong (Universiti Teknologi PETRONAS, 2020)
Pantai Teluk Nipah is facing gradual coastal erosion since the occurrence of severe storm events in the year 2017. This issue has alarmed the local stakeholders and community as their economy is threatened. Coastal erosion has been causing various structural damages on the tourist chalets and businesses operating by the beach. In the past, the longshore sediment transport rate at Pantai Teluk Nipah has not been determined using sediment traps (field study) and empirical formulae (empirical study). Following the abovementioned issue, two site studies were carried out to study the shoreline changes due to longshore sediment transport for spring tide and neap tide on 10th to 12th February and 17th to 18th February respectively.